Communicating to connect with patients. (January 2023) - McCabe, Rose
SUMMARY: Michaelson & Rahim describe a very welcome sustainable training framework for teaching clinical communication skills to trainees on MRCPsych courses. This commentary expands on their article, noting how psychiatrists listen and ask questions affects the therapeutic relationship and patients' willingness or ability to disclose sensitive information, which is particularly important in risk assessment. Extending videorecording role-plays in training to routine (including remote) clinical consultations and involving patients and carers in training will be key to identifying communication that has a positive impact on patient experience and outcomes.